Inﬂuence of substrate temperature on the microstructure of TiN/TiC (2011)
The TiN / TiC bilayers were deposited using the plasma-assisted vapor phase deposition (PAPVD) -Arch Pulsed technique, varying the substrate temperature in a range of 100-120 ± C, with intervals of 5 ± C. The coatings were analyzed by means of XPS and XRD. From the treatment of the signals of the narrow spectra of XPS and the XRD patterns, the formation of the compounds TiN (Titanium Nitride), TiC (Titanium Carbide) and TiCN (titanium carbide) in the crystallographic phase was determined fm-3m corresponding to the FCC phases of these synthesized compounds.